Development of Short Story Appreciation TextbookUsing Contextual Approach at Junior Secondary Schools - Susilowati, Dwi; Nurkamto, Prof. Dr. Joko; Waluyo, Prof. Dr. Herman J.; Suwandi, Prof.Dr. Sarwiji; Andayani, Prof. Dr. (IJRDO- Journal of Educational Research, 2017)
Short story appreciation learning enables the students to reach the languagelevel of appreciation, expression, and creation. In short story learning, the aspect ofappreciation has not been emphasized. It happens due to unfamiliarity with various kindsofshort story. Besides, the learning process is only dominated by teachers due to the limitednumber of short story appreciation textbooks.This research applied the R&D method with thefollowing stages: (1)exploration; (2) model development; (3) model testing; and (4)dissemination. Through the stages, a short stoy appreciation textbook for Junior SecondarySchools was designed.The model development was done through the stages of textbookdrafting, limited textbook testing, extended textbook testing, and workshop with expertjudgement.The designed textbook includedconstructivism, inquiry, learning community,inquiry exercise, modeling, reflection and autehtic assessment.The result of this researchshows that in the learning process of short story appreciation,a reliable textbookwasrequired.The textbook was experimentally reliable and significant. It was also acceptable inthe dissemination stage.